A Squatter Community as the Keeper of Cultural Heritage: Interaction Between Spatial and Social Bonding Processes. (1st May 2013) - Van Dam, R.I.; Termeer, C.J.A.M.; Van der Zande, A.N.
Abstract : In this article, an analysis is made of the social and spatial bonding processes affecting a squatter community who lived at Fort Pannerden in the Netherlands for about seven years. Besides describing the relation between the squatters and the fort, the article analyses the influence of the squatters' actions on the development of the fort and on the local community and local governmental organizations in terms of social and spatial bonding processes. We demonstrate how a non-institutional actor, a squatter community, was able to bring a national monument, which had been disused for several decades, back to life—reconnecting a cultural heritage site to society and vice versa.